IMPLEMENTASI METODE ADAPTIVE SOFTWARE DEVELOPMENT (ASD) PADA PENGEMBANGAN SISTEM INFORMASI MADRASAH DINIYAH ULA HIDAYATUL FALAH DESA DONO KECAMATAN SENDANG KABUPATEN TULUNGAGUNG BERBASIS WEB - Okta Mayasari, Anisa; Agung Cahyono, Taufiq; Kartika Sari, Yayak (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by problems in administrative management at Madrasah Diniyah Ula Hidayatul Falah, which are still carried out manually, such as student data management, attendance, new student admission (PPDB), scheduling, and information dissemination, resulting in inefficiency and a high risk of errors. The purpose of this study is to implement the Adaptive Software Development (ASD) method in developing a web-based information system and to evaluate the results of system development in accordance with user needs. The method used is Adaptive Software Development (ASD) with three stages: Speculation, Collaboration, and Learning. Data collection techniques include observation, interviews, literature study, and documentation. The system is developed using the Laravel framework, PHP programming language, and MySQL database. The results show that the developed web-based information system is able to improve data management, making it more effective, structured, and easily accessible. The implementation of ASD provides flexibility in system development, enabling it to adapt to changing user requirements. Therefore, this system is expected to improve the quality of administrative services and facilitate information delivery to administrators, teachers, and students’ guardians.